PENINGKATAN KUANTITAS DAN KUALITAS PRODUK PERAJIN HANDICRAFT PERCA DAN BORDIR KSM â€œKESRAâ€ KELURAHAN KEDURUS, KOTA SURABAYA - Sri Andayani; Indah Murti; Sajiyo Sajiyo (JPM17: Jurnal Pengabdian Masyarakat, 2015)
Handicraft industry in Surabaya had grown 7% -10% in the last two years. One Small and Middle Enterprise engaged in handicraft in Surabaya is KSM "Kedurus prosperous" or "Welfare". KSM worked on patchwork combined with a variety of fabrics to make various handicrafts. The problem was the capability of production was still very limited due to the lack of owned equipment. To overcome the problem the implementer partner conducted some activities including: supplying the needed machinery and equipment; training skills to use tools and machines applying learning by doing method;Â  assisting marketing process by: training techniques and marketing strategy - making media marketing, brochures, banners. The achieved results were: buying 2 units of Wolking-foot machine for 2 Partners,Â  buying 2 unit mowers for 2 Partners; buying 2 units of measuring and cutting tables for 2 partners; printing brochures as many as 1000 pieces and 2 banners; as well as the training of use equipment and machine and the training of bookkeeping and entrepreneurship, marketing and business management. To conclude, the activity IbM is very helpful for those who did the creative economy of small businesses such as patchwork handicraft in Surabaya to improve the quality and quantity of their products.Key words : Patchwork handicraft,Â  KSM â€œ Kedurus Sejahteraâ€